2009
DOI: 10.1093/ndt/gfp372
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, crossover design study of sevelamer carbonate powder and sevelamer hydrochloride tablets in chronic kidney disease patients on haemodialysis

Abstract: Background. Sevelamer carbonate is an improved, buffered form of sevelamer hydrochloride developed for the treatment of hyperphosphataemia in CKD patients. Sevelamer carbonate formulated as a powder for oral suspension presents a novel, patient-friendly alternative to tablet phosphate binders. This study compared the safety and efficacy of sevelamer carbonate powder with sevelamer hydrochloride tablets in CKD patients on haemodialysis.Methods. This was a multi-centre, open-label, randomized, crossover design s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 13 publications
(5 reference statements)
0
37
0
Order By: Relevance
“…2,3 In summary, both Genz-644470 and sevelamer carbonate effectively lowered hemodialysis patients' serum phosphorus levels in a dose-dependent fashion, but Genz-644470 did not show an advantage in phosphorus lowering in dialysis patients compared with sevelamer carbonate, as had been demonstrated by an in vitro assay. [6][7][8] Author contributions MM, contributing study investigator, contributed to multiple iterations of the manuscript text.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…2,3 In summary, both Genz-644470 and sevelamer carbonate effectively lowered hemodialysis patients' serum phosphorus levels in a dose-dependent fashion, but Genz-644470 did not show an advantage in phosphorus lowering in dialysis patients compared with sevelamer carbonate, as had been demonstrated by an in vitro assay. [6][7][8] Author contributions MM, contributing study investigator, contributed to multiple iterations of the manuscript text.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies of sevelamer have shown significant phosphate lowering within 1 week with small, incremental lowering at 2 weeks. 2,11,12 Therefore, the 3-week observation period employed in this study was considered of sufficient duration for an initial comparison of the efficacy of Genz-644470 and sevelamer carbonate in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the earlier Cochrane review (8), sevelamer and CBBs did not differ significantly for end of study serum phosphate. Serum bicarbonate values were lower with sevelamer (hydrochloride and carbonate coanalyzed), likely reflecting the lower buffering capacity of sevelamer hydrochloride than Ca carbonate (46,47).…”
Section: Discussionmentioning
confidence: 99%